Assessment of Policy Changes of the Impacts of Urbanization, Economic Growth and Decentralization of Water Services with Regard to Water Quality in Mexico - Lara Cervantes, René Fernando; Šauer, Petr; Dvořák, Antonín; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The thesis studies the case of water quality in Mexico as a crucial factor to prevent water scarcity. This is an important issue for Mexico since more than half of its territory is arid or semi-arid; moreover, the most productive regions are located in areas with significant water resources stress. In this regard, the current situation of water scarcity is studied from the changes in water management derived from the evolution of institutions in the country. The institutional changes were analyzed mostly in the transition from a centralized water supply and sanitation services with strong state intervention to the decentralization of such services that were transferred to municipalities. Decentralization was addressed by analyzing the performance of water supply and sanitation services in urban areas that are expected to continue growing in the near future. The literature shows that the decentralization process has been partial and has not improved as expected the performance of water supply and sanitation services, moreover, due to political reasons, limited human and financial resources it introduced more challenges to the accomplishment of sustainable water management. More importantly, the federal government is still the main agent for the development of the water sector in Mexico. The next part of the analysis consist of a quantitative and qualitative evaluation regarding water quality for the three most productive Hydrological-Administrative Regions (HARs) of Mexico in the period of 2003-2013. The HARs chosen are the HAR VI Río Bravo, HAR VIII Lerma Santiago Pacific and HAR XIII Waters of the Valley of Mexico which are very similar in terms GDP share and water stress degree. Through OLS regression models for each HAR the impacts of demographic, economic, water supply and sanitation services aspects were tested to known their effects on water quality.
In order to improve the discussion of the results, additional to the comparison with the results of the literature review, three experts were asked to answer a questionnaire about the regressions outcome. The discussion showed different impacts of the independent variables in the dependent variable of each HAR, sometimes leading to unexpected results. The main conclusions of the thesis relate to the improvement of decentralization of water and sanitation services, to the need to improve data for future analyses and pay more attention to water quality issues. In this regard, decentralization requires to consider contextual differences in order to seize its advantages to improve the performances of water supply and sanitation services, moreover, at the operative level water management decisions must be taken without political interests involved. The statistical analyses stressed the need to develop more reliable data about water management issues to improve the understanding of factors that could potentially affect water quality. In this regard, the creation of useful statistical indicators to assess the evolution towards sustainability in water management. The considerations for future research must consider more seriously water quality issues. This topic has been often ignored, however, it is crucial for water scarcity abatement.
Vedoucí práce: Petr Šauer
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: politologie [obor disert. práce]; disertace; dissertations